(untitled) (Raparin Journal of Humanities (RJH), 2024)
The current study aims to know the main causes of marital in fidelity &its impact on families and children in particular & on society in general . The study merstigates the preralence of marital infidelity its types it also attempts to discover the motivating factors that leads to conduct this act in addition, the impact of such action in addition, the impact of such action on families as well as various of betrayal methods to prevent the spread of betrayal is also identified by the researcher The type of the study is qualitative& description approach is used by the research to study the case & the interview with observation tools are used to collect data with narrative tools to singinfy on the case research. The researcher took 5cases in Erbil city center .samples are from several governmental institutions thar are specialized in reform, adoption also protecting individuals from Any from of violence or Threat. For instance, Erbil Shelter Directorate, women &Children reform Directorate ,Detention &transfer Directorate) The study concludes thar one of the main reason for infedility in most of the cases is the feeling of revenge that one of the spouses hold against the other due to the absence of the partner that creates an emotional & sexual gap & leads to neglect. In addition, imitating dubbed dramas had an impact on prevalence of this phenomenon.